Teachers’ Competence Among the Student Teachers: An Analysis of Self-Reflective Feedback in Microteaching Class - Paulina Besty Fortinasari; Carolus Prima Ferri Karma; Dwi Winarsih (Universitas Tidar, 2023)
No one denies that currently teaching becomes more challenging. One of the ways to produce competent and qualified English teacher is by conducting microteaching class. Microteaching class is one of the prerequisites courses before the student teachers take the real teaching practice done in senior or junior high schools. This paper focuses on the self-reflective feedback done by the student teachers in microteaching class and how the student teachers respond to the application of self-reflective feedback in Microteaching Class. The data gathered from online reflection form, online questionnaire and interview showed that self-reflective feedback is helpful for the student teachers in assessing and analyzing their teaching performances. The student teachers also gave positive responses on the use of self-reflective feedback in the Reflective Microteaching Class. In addition, the student teachers need guidance from the lecturer in doing self-reflective feedback and therefore, their understanding and competencies in teaching are more developed.